A history of ancient Near Eastern law - Westbrook, Raymond.; Beckman, Gary M. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2003)
The first comprehensive survey of the world's oldest known legal systems, this collaborative work of twenty-two scholars covers over 3,000 years of legal history of the Ancient Near East. Each of the book's chapters represents a review of the law of a particular period and region, e.g. the Egyptian Old Kingdom, by a specialist in that area. Within each chapter, the material is organized under standardized legal categories (e.g. constitutional law, family law) that make for easy cross-referencing. The chapters are arranged chronologically by millennium and within each millennium by the three major politico-cultural spheres of the region: Egypt, Mesopotamia, and Anatolia and the Levant. An introduction by the editor discusses the general character of Ancient Near Eastern Law.